Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1164/rccm.200812-1901oc
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Multipotent Progenitors from the Peripheral Blood of Patients Requiring Extracorporeal Membrane Oxygenation Support

Abstract: Hematopoietic, mesenchymal, and epithelial progenitors were mobilized into the circulation of patients on ECMO. This may reflect a response to severe cardiopulmonary injury, blood-foreign surface interactions with the ECMO circuit, and/or hemodilution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 65 publications
(85 reference statements)
2
16
0
1
Order By: Relevance
“…Mesenchymal stem cells (MSCs) are adult stem cells that are found in the bone marrow [40], cord blood [41] and peripheral blood of human infants with severe acute life threatening respiratory failure who require extracorporeal life support [42]. Intra-pulmonary administration of bone marrow MSCs noticeably decrease inflammatory responses and improve survival in an endotoxin model of lung injury in mice [43].…”
Section: The Role Of Bone Marrow Derived Cell Types and Soluble Factomentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are adult stem cells that are found in the bone marrow [40], cord blood [41] and peripheral blood of human infants with severe acute life threatening respiratory failure who require extracorporeal life support [42]. Intra-pulmonary administration of bone marrow MSCs noticeably decrease inflammatory responses and improve survival in an endotoxin model of lung injury in mice [43].…”
Section: The Role Of Bone Marrow Derived Cell Types and Soluble Factomentioning
confidence: 99%
“…A study in patients requiring extracorporeal membrane oxygenation for life support found that hematopoietic, mesenchymal, and epithelial cell progenitors were mobilized into the circulation, suggesting that progenitor cell mobilization may be a mechanism of nonresident progenitor cell recruitment to injured tissues (73).…”
Section: Apoptosis Degradation Proliferation and Progenitor And Stmentioning
confidence: 99%
“…Mit Erholung der Lungenfunktion kann die extrakorporale Unterstützung wieder reduziert werden kann. Ob die Mobilisation von pluripotenten Stammzellen, welche aus ECMO-Kreisläufen isoliert werden können, die Reparaturmechanismen in den Patientenlungen unterstützt, ist Gegenstand eines neueren Forschungsansatzes [4]. Wenn bei VA-EC-MO der Blutfluss auf 20% des Herzzeitvolumens reduziert werden kann, ohne dass die systemvenöse Sättigung (S v O 2 ) unter 70% fällt, beginnt die sog.…”
Section: Prä-ecmounclassified